Neuraminidase 1 regulates neuropathogenesis by governing the cellular state of microglia via modulation of Trem2 sialylation - Leigh Ellen Fremuth; Huimin Hu; Diantha van de Vlekkert; Ida Annunziata; Jason Andrew Weesner; Alessandra d’Azzo (Cell Reports)
Summary: Neuraminidase 1 (NEU1) cleaves terminal sialic acids from sialoglycoproteins in endolysosomes and at the plasma membrane. As such, NEU1 regulates immune cells, primarily those of the monocytic lineage. Here, we examine how Neu1 influences microglia by modulating the sialylation of full-length Trem2 (Trem2-FL), a multifunctional receptor that regulates microglial survival, phagocytosis, and cytokine production. When Neu1 is deficient/downregulated, Trem2-FL remains sialylated, accumulates intracellularly, and is excessively cleaved into a C-terminal fragment (Trem2-CTF) and an extracellular soluble domain (sTrem2), enhancing their signaling capacities. Sialylated Trem2-FL (Sia-Trem2-FL) does not hinder Trem2-FL-DAP12-Syk complex assembly but impairs signal transduction through Syk, ultimately abolishing Trem2-dependent phagocytosis. Concurrently, Trem2-CTF-DAP12 complexes dampen NF-κB signaling, while sTrem2 propagates Akt-dependent cell survival and NFAT1-mediated production of TNF-α and CCL3. Because NEU1 and Trem2 are implicated in neurodegenerative/neuroinflammatory diseases, including Alzheimer disease and sialidosis, modulating NEU1 activity represents a therapeutic approach to broadly regulate microglia-mediated neuroinflammation.